Les transformations du travail des opérateurs de raffinerie de pétrole : le passage des cadrans aux écrans - Raymond Baril (Perspectives Interdisciplinaires sur le Travail et la Santé)
Interview material from retired and former oil refinery plant operators concerning 12-hour shifts reveals parallel thoughts about the nature of the operators’ work and, more specifically, control room automation. The advent of computerized control rooms has changed the operators’ perception of their role in controlling the production process. Automation and the ensuing personnel cutbacks have profoundly altered both teamwork and work strategies for production and site safety. Former operators now evoke isolation, insecurity, stress and even exclusion in discussions about control room automation.